A systematic literature review on electromagnetic wave propagation challenges in 5G/6G mmWave and THz bands and emerging physics informed mitigation strategies - Mutiara Putri; Diah Nurvita; Hamdi Akhsan (Journal of Physics: Theories and Applications, 2026)
Basic physics governs the propagation of electromagnetic waves in the millimeter wave (mmWave: 24–100 GHz) and terahertz (THz: 0.1–10 THz) ranges, as well as Maxwell's equations, molecular resonance phenomena, and the dielectric response of materials. Although 5G and 6G systems utilize these high frequency ranges to achieve terabit per second data rates, their performance is inherently limited not by technical constraints, but by the intrinsic interaction of waves with matter. The main physical obstacles include atmospheric absorption due to water vapor, free space path loss that increases quadratically with frequency, and extremely shallow skin depth in common building and biological materials, making even thin barriers highly impervious to mmWave and THz signals. This paper provides a systematic literature review (SLR) that was carried out following the recommendation of PRISMA 2020 to synthesize physics grounded propagation challenges and mitigation strategies. From an initial collection of 46 Scopus indexed and peer reviewed articles published between 2020 and 2025, 20 high quality studies were selected for thematic synthesis based on a five-point methodological checklist. The study demonstrates that novel approaches like AI-based channel modeling cell-free Massive MIMO FeO₃ enriched building composites and Reconfigurable Intelligent Surfaces (RIS) strategically use wave interference tunable permeability and real-time environmental awareness to improve signal delivery rather than breaking the laws of physics. By bridging the conceptual divide between communications engineering and basic electromagnetics this study provides a cohesive physics framework that will direct future studies in 5G and 6G wireless systems.